1983
DOI: 10.1161/01.res.53.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of positive inotropic agents on the relation between oxygen consumption and systolic pressure volume area in canine left ventricle.

Abstract: SUMMARY. We analyzed the effect of positive inotropic agents on the relation between left ventricular oxygen consumption and the systolic pressure-volume area. Pressure-volume area is a measure of total mechanical energy for ventricular contraction, and is a specific area in the ventricular pressure-volume diagram circumscribed by the end-systolic and end-diastolic pressurevolume relation curves and the systolic segment of the pressure-volume trajectory. Either epinephrine (1 Mg/kg per min, iv) or calcium ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
186
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(196 citation statements)
references
References 43 publications
9
186
1
Order By: Relevance
“…This efficiency value does not change much even if the mechanical work per beat is doubled by the use of a substrate such as pyruvate or by the use of inotropic agents such as ouabain or isoprenaline [129,130]. These results are consistent with the constant contractile efficiency measured by Suga and colleagues [103,123] in the presence of agents that alter cardiac contractility. It can be argued that the net mechanical efficiency of afterloaded papillary muscles is overestimated by the recoil of the stretched parallel elastic elements [131][132][133], but because in vivo and in isolated working hearts the ventricles are stretched in diastole by the returning venous blood, we believe that the isolated papillary muscle model approximates reality and that the net efficiency of the heart is close to 20%.…”
Section: Basal Metabolism Mechanical Efficiency and Species Difsupporting
confidence: 87%
“…This efficiency value does not change much even if the mechanical work per beat is doubled by the use of a substrate such as pyruvate or by the use of inotropic agents such as ouabain or isoprenaline [129,130]. These results are consistent with the constant contractile efficiency measured by Suga and colleagues [103,123] in the presence of agents that alter cardiac contractility. It can be argued that the net mechanical efficiency of afterloaded papillary muscles is overestimated by the recoil of the stretched parallel elastic elements [131][132][133], but because in vivo and in isolated working hearts the ventricles are stretched in diastole by the returning venous blood, we believe that the isolated papillary muscle model approximates reality and that the net efficiency of the heart is close to 20%.…”
Section: Basal Metabolism Mechanical Efficiency and Species Difsupporting
confidence: 87%
“…Figure 3 shows that the additional relaxation (difference in relaxation between ϩT and ϪT segments) due to the surrounding myocardial tissue is larger than the relaxation of the vessel alone (ϪT segments). It should be noted that the energy need of the cardiac tissue in our preparation is primarily determined by basal metabolism, whereas in actively contracting tissue, the energy need is also determined by excitation-contraction coupling metabolism and mechanical activity associated with cross-bridge turnover (29). Therefore, the contribution of the cardiac myocytes in the beating heart is expected to be stronger.…”
Section: Myocardial Tissuementioning
confidence: 99%
“…The E max -PVA-VO 2 framework is compatible with the Starling law of the heart [9]. In this framework, the O 2 cost of E max serves as a physiologically sound quantitative measure of the O 2 demand for unit increment in E max [5,[10][11][12][13][14][15][16].We have already shown that calcium, catecholamines, digitalis, and phosphodiesterase inhibitors (DPI 201-106, OPC-8212, EMD-53998, milrinone, sulmazole, etc.) have comparable O 2 cost of E max in the normal canine heart [5,10,11,15].…”
mentioning
confidence: 98%
“…In this framework, the O 2 cost of E max serves as a physiologically sound quantitative measure of the O 2 demand for unit increment in E max [5,[10][11][12][13][14][15][16].…”
mentioning
confidence: 99%